Addressing The Uncertain Future of Agriculture in Nepal: Agents of Food System Changes and Immediate Need for Intervention - Uprety, Sudan Prasad; Hindle, Tobin (Himalayan Biodiversity, 2025)
Food systems are complex and dynamic in the sense that they are affected not just by the amount of food produced and available but by several social, physical, cultural, environmental, and economic aspects of farming households.. It is imperative to study the agents of such changes in food systems and plan, develop, and adopt site and locally specific mitigation measures to ensure the continuation of agricultural practices to move closer towards a sustainable and food secure region. The study among 245 respondents from Chitwan, Dhading, and Rasuwa districts revealed that the major drivers of food system changes in these districts were a lack of agricultural labour, a lack of government support, crop damage by wildlife, land abandonment, and shifts in occupation. Along with these factors, increased outmigration in the districts from rural to city and more urban areas, climate change, better and improved access to markets and processed foods in the markets act as major drivers of food system changes in these districts. Small-scale and community-targeted Farming, along with complementary food forest systems, along with economic incentives for young populations from rural areas, might be the key to continuing subsistence farming and promoting commercial farming in potential districts. Activities such as better infrastructure for agriculture (i.e., irrigation, markets, storage facilities, roads, and electricity), providing subsidies for farming communities, increased training for better production, crop insurance, better farming techniques, and enhancing farming households' economic status and buying capacity are crucial for reducing the increasing uncertainty in agriculture.